Reconfiguração de alimentadores em sistemas de distribuição usando uma metaheurística e espaço de busca reduzido - Fioravanti Junior, Celso [UNESP] (2014)
In this paper, Chu-Beasley’s specialized genetic algorithm will be used to solve the reconfiguration of distribuition system problem, which was modeled such as mixed integer nonlinear programming problem. In this work was defined a reduced search space to reduce the computational time of genetic algorithm of Chu-Beasley’ specialized to solve the reconfiguration of distribution systems problem. To evaluate the feasibility regarding constraints of the electrical power systems' operation, an algorithm for radial load flow was implemented to calculate these nodal tensions of these systems and, losses and currents of the system. Tests are presented using the systems of 14, 33, 84, 119 and 417 buses to avaluate the efficiency and robustness of the proposed method. The results were presented and compared to those found in the literature